The topology of connections between rat prefrontal, motor and sensory cortices - Bedwell, Stacey A.; Billett, E. Ellen; Crofts, Jonathan J.; Tinsley, Chris J. (Frontiers in Systems Neuroscience, 2014)
The connections of prefrontal cortex (PFC) were investigated in the rat brain to determine the order and location of input and output connections to motor and somatosensory cortex. Retrograde (100nl Fluoro-Gold) and anterograde (100nl Biotinylated Dextran Amines; Fluorescein and Texas Red) neuronanatomical tracers were injected into the subdivisions of the prefrontal cortex (prelimbic, ventral orbital, ventrolateral orbital, dorsolateral orbital) and their projections studied. We found clear evidence for organised input projections from the motor and somatosensory cortices to the prefrontal cortex, with distinct areas of motor and cingulate cortex projecting in an ordered arrangement to the subdivisions of prefrontal cortex. As injection location of retrograde tracer was moved from medial to lateral in PFC, we observed an ordered arrangement of projections occurring in sensory-motor cortex. There was a significant effect of retrograde injection location on the position of labelled cells occurring in sensory-motor cortex (dorsoventral, anterior-posterior and mediolateral axes p<.001). The arrangement of output projections from prefrontal cortex also displayed a significant ordered projection to sensory-motor cortex (dorsoventral p<.001, anterior-posterior p=.002 and mediolateral axes p<.001). Statistical analysis also showed that the locations of input and output labels vary with respect to one another (in the dorsal-ventral and medial-lateral axes, p<.001). Taken together, the findings show that regions of prefrontal cortex display an ordered arrangement of connections with sensory-motor cortex, with clear laminar organisation of input connections. These results also show that input and output connections to prefrontal cortex are not located in exactly the same sites and reveal a circuit between sensory-motor and prefrontal cortex.